Trends and benefits of online distance learning in the English as a second language context: a systematic literature review - Zainuddin, Nur Mazliyana; Mohamad, Maslawati; Zakaria, Nur Yasmin; Sulaiman, Nur Ainil; Jalaludin, Nur Atiqah; Omar, Halizah (Arab World English Journal, 2024)
The COVID-19 pandemic has shifted the education field across the globe. This transformation has made education more accessible through the emergence of online distance learning. Therefore, this systematic literature review presents an extensive review and analysis of existing studies on online distance learning in the English as a Second Language context. The study’s main aim is to explore the effectiveness of online distance learning in the English as a Second Language context. The significance of the study lies in its potential to inform educational stakeholders about the advantages and areas for improvement in online distance learning for learners and teachers, thus enhancing educational practices and policies. The primary research question guiding this review is: What are the experiences and perceptions of teachers and students regarding online distance learning in the English as a Second Language context? The study follows the PRISMA 2020 statement guidelines for systematic literature reviews, investigating peer-reviewed articles from the SCOPUS and ERIC databases (2019 – 2023). Seventeen (17) studies were selected based on the inclusion and exclusion criteria. The findings indicate growing research interest in online distance learning in the English as a Second Language context. Most of the studies employed qualitative design in which university students mainly were used as participants. The findings also provide invaluable insights regarding the benefits enjoyed by both students and teachers from online distance learning. Key benefits derived from students’ perceptions are comfort, enjoyable, time-saving, autonomous learning, improved communication, and collaborative skills. Teachers, on the other hand, stated that the benefits they enjoyed through online distance learning were time savings, a positive learning environment, improved teaching efficiency, money savings, and enhanced students' psychological factors. To summarise, these findings suggest that stakeholders should take the appropriate measures to effectively implement online distance learning and achieve Sustainable Development Goal 4 (SDG4), which aims to ensure inclusive and equitable education for all.